Exhumation of the Neuquén Basin in the southern Central Andes (Malargüe fold and thrust belt) from field data and low-temperature thermochronology - Folguera Telichevsky, Andres (2015)
Apatite fission-track analysis performed on eighteen Mesozoic sediment samples of the Neuquén Basin from the Southern Central Andes orogenic front between 35°30′ and 37°S has revealed Campanian-Paleocene (75-55 Ma), late Eocene-early Oligocene (35-30 Ma) and middle Miocene (15-10 Ma) cooling episodes. Each cooling episode corresponds closely with major unconformities observed in the preserved sedimentary sequences, and is associated with kilometer-scale additional burial and subsequent exhumation. A similar degree of cooling is inferred from associated vitrinite reflectance data. Late Eocene-early Oligocene exhumation is recognized only near the eastern orogenic front adjacent to the foreland in the southernmost part of the study area and may be related partly to within-plate magmatism and associated extension in the Palaoco Basin. The Campanian-Paleocene and middle Miocene cooling episodes are recognized more widely in the fold and thrust belt and appear to coincide with periods of eastward arc expansion and mountain building processes.